PENGARUH LEMON KALAMANSI (Citrus microcarpa) TERHADAP KOMPOSISI KIMIA DAN FITOKIMIA ANTIOKSIDAN DARI TEPUNG PISANG GOROHO (Musa spp.) - Suryanto, Edi; Momuat, Lidya; Taroreh, Mercy; Wehantouw, Frenly (Sam Ratulangi University, 2011)
ABSTRACTSuryanto et al., 2011. Effect of callamansi citrus (Citrus microcarpa ) on chemical composition and antioxidantphytochemical of Goroho (Musa spp.) banana flour.The objective of this research was to study chemical composition and measured antioxidant activity of gorohobanana flour which immersed with callamansi. The goroho banana was soaked with water, callamansi andsodium methabisulfit for 60 minute. Furthermore, each flour were analyzed its phytochemical such as,proximate analysis, total phenolic content, flavonoid, condensed tannin, carotenoid, ascorbic acid, totalantioxidant using titration and spectrophotometer method. The results showed that callamansi addition of 1%was the best treatment for banana flour. The product had content of moisture, ash, fat, protein, fiber andcarbohydrate were 4.29 ± 0.01; 3.74 ± 0.02; 3.03 ± 2,04; 1.47 ± 0.57; 4.75 ± 0.57 and 85.70 ± 0.59,respectively. The banana flour soaked with callamansi for 60 minute had phenolic, flavonoid, condensed tannintotal content were 55.82 ± 0,01; 6.27 ± 0.08 and 36.50 ± 0.24 mg/kg, respectively. Whereas ascorbic acid andcarotenoid total content of goroho banana flour were 51.92 ± 3.73 and 6.36 ± 1.13mg /kg sample, respectively.Total antioxidant of banana flour extract soaked with callamansi shows high activity compared without soakedand soaked with sodium methabisulfit for 60 minute. The results showed that banana flour immersed withcalamansi extract and sodium metabisulfit possess different proximate composition (p<0.05). Banana immersedwith calamansi extract appears to increase phenolic, flavonoid, condensed tannin, ascorbic acid content as wellas the capacity antioxidant of banana four.Keywords : goroho banana, proximate, flour, callamansi, antioxidant phytochemical